Financial dollarization: Short-run determinants in transition economies - Neanidis, Kyriakos C.; Savva, Christos S. (My University, 2009)
This paper examines the determinants of financial dollarization in transition economies from a short-run perspective. Using aggregate monthly data of deposit and loan dollarization we study the drivers of short-term fluctuations in dollarization and test their importance at different levels of dollarization. The results provide evidence that (a) the positive (negative) short-run effects of depreciation (monetary expansion) on deposit dollarization are exacerbated in high-dollarization countries; (b) short-run loan dollarization is mainly driven by banks matching of domestic loans and deposits, currency matching of assets and liabilities, international financial integration, and institutional quality; and (c) both types of short-run dollarization are affected by interest rate differentials and deviations from desired dollarization.
Keywords: Currency risk; Financial dollarization; Short-run variations; Transition economies; Currency risk; Financial dollarization; Short-run variations; Transition economies